Child protection in the northern states of Nigeria : a need for a new child law - Alkali, Alhaji Umar (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
Islamic law and the Convention on the Rights of the Child (CRC) have provided for the protection of the rights of children. The rights to life, health, dignity, religion and family are part of the body of rights guaranteed to every child by both regimes. Though the two regimes have much in common in terms of protection provided for the child, there are however areas where they disagree. Freedom of religion, child marriage, best interest of the child, age of maturity and adoption are areas where the two regimes substantially disagree. Several Muslim States have tendered reservations on the provisions of the CRC that are considered as contrary to Islamic law. Though Nigeria ratified the CRC without reservation, most of the states in Northern Nigeria declined to domesticate the CRC for its perceived conflict with Islamic law. The Child's Right Act 2003 which applies in the Federal Capital Territory, Abuja came on board upon domestication of the CRC by the National Assembly. For most of the Northern States with Muslim majority, there is still no legislation that is dedicated to child protection that provides for the protection of the rights of the child, the result thereof is the absence of a legal framework on child protection in most of the Muslims states of Northern Nigeria. Doctrinal and empirical methodologies were used in discussing the rights of children under Islamic law and the Convention on the Rights of the Child. The same methodologies were used in discussing the effect of their conflict on children in most of the states in Northern Nigeria. Further, comparative methodology was used in examining the conflict between the two regimes and historical methodology was used in tracing the historical backround of some issues discussed in the thesis. This study found out that the scenario has negatively affected millions of children in the area of health, education and dignity. The almajiri phenomenon is a reflection of the bitter reality affecting children in the Northern states. The way out of this unfortunate situation is therefore the promulgation of a law on child protection based on Islamic principles for the states of Northern Nigeria so that it will be accepted by the Muslim majority who are skeptical of the Child's Right Act 2003 and consider it a Western ideology that is aimed at taking Muslim children out of the control of their parents and surrender them to the proxies of the West